Analisis Kisah Para Rasul 15 Tentang Konflik Paulus dan Barnabas serta Kaitannya dengan Perpecahan Gereja - Sonny Eli Zaluchu (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2018)
AbstractThe separation of Paul and Barnabas in Acts 15 is often used as a ground of foundation for the occurrence of separation or precisely, division, in the church and ministry. This article attempts to review the root causes of the conflict between Paul and Barnabas as a reflection for the church in dealing with and managing conflict. The separation of Paul and Barnabas as a biblical foundation for supporting church division/service for the noble purpose of evangelism is not right and out of biblical paradigm. The ongoing conflict between Paul and Barnabas was not a conflict that gave rise to hostility, rivalry or an attitude of attack as the phenomenon commonly encountered in church or ministry. The separation of Paul and Barnabas is a strategic decision that results in expanding the range of the spread of the gospel of Christ.AbstrakPerpisahan Paulus dan Barnabas di dalam Kisah Para Rasul 15 sering menjadi alasan bagi terjadinya permisahan, atau tepatnya perpecahan, di dalam gereja dan pelayanan. Artikel ini mengulas akar masalah konflik Paulus dan Barnabas sebagai refleksi bagi gereja dalam menghadapi dan mengelola konflik yang mengarah pada perpecahan. Menggunakan perpisahan Paulus dan Barnabas sebagai patron alkitabiah untuk mendukung perpecahan gereja atau pelayanan dengan alasan demi pekabaran Injil, rasanya kuranglah tepat. Konflik yang berlangsung antara Paulus dan Barnabas bukanlah konflik yang melahirkan sikap permusuhan, persaingan atau sikap saling serang sebagaimana fenomena yang umum ditemui di dalam perpecahan gereja/pelayanan. Perpisahan Paulus dan Barnabas adalah sebuah keputusan strategis yang menghasilkan perluasan jangkauan penyebaran Injil Kristus.